Crosslinking methods in bioplastic production a review. - Navarra, Justine Nagamos
Bioplastics are plastics produced from renewable biomass source. Because of the demand for sustainable use of plastics, a gap needs to be addressed between bioplastics and conventional plastics. Crosslinking is introduced as a method to improve the mechanical properties and physical properties of the bioplastics. Studies published from 2011 to 2022 were collected and gathered information to synthesize a review article. This review provides a detailed discussion on the crosslinking methods in bioplastic production through the identification of biopolymers and crosslinking agents used in bioplastic production, the synthesis of crosslinking of bioplastics, characterization of crosslinked bioplastics, the assessment of the bioplastics through the mechanical properties such as tensile strength, elongation at break, and Young's modulus, physical properties such as water vapor permeability and water solubility, and the biodegradability if the bioplastics. The bioplastics included in this review are applicable to various applications such as food packing, medical applications, and agricultural applications.